Crustacean hyperglycemic hormone (cHH) as a modulator of aggression in crustacean decapods. - Laura Aquiloni; Piero G Giulianini; Alessandro Mosco; Corrado Guarnaccia; Enrico Ferrero; Francesca Gherardi (PLoS ONE)
Biogenic amines, particularly serotonin, are recognised to play an important role in controlling the aggression of invertebrates, whereas the effect of neurohormones is still underexplored. The crustacean Hyperglycemic Hormone (cHH) is a multifunctional member of the eyestalk neuropeptide family. We expect that this neuropeptide influences aggression either directly, by controlling its expression, or indirectly, by mobilizing the energetic stores needed for the increased activity of an animal. Our study aims at testing such an influence and the possible reversion of hierarchies in the red swamp crayfish, Procambarus clarkii, as a model organism. Three types of pairs of similarly sized males were formed: (1) 'control pairs' (CP, n = 8): both individuals were injected with a phosphate saline solution (PBS); (2) 'reinforced pairs' (RP, n = 9): the alpha alone was injected with native cHH, and the beta with PBS; (3) 'inverted pairs' (IP, n = 9): the opposite of (2). We found that, independently of the crayfish's prior social experience, cHH injections induced (i) the expression of dominance behaviour, (ii) higher glycemic levels, and (iii) lower time spent motionless. In CP and RP, fight intensity decreased with the establishment of dominance. On the contrary, in IP, betas became increasingly likely to initiate and escalate fights and, consequently, increased their dominance till a temporary reversal of the hierarchy. Our results demonstrate, for the first time, that, similarly to serotonin, cHH enhances individual aggression, up to reverse, although transitorily, the hierarchical rank. New research perspectives are thus opened in our intriguing effort of understanding the role of cHH in the modulation of agonistic behaviour in crustaceans.